Pre-harvest and post-harvest farmer experiences and practices in five maize growing regions in Ghana - Darfour, Bernard; Rosentrater, Kurt A. (Frontiers in Nutrition, 2022)
Maize is a major staple crop mainly produced by smallholder farmers in developing nations. Grain losses happen in Sub-Saharan Africa, and therefore the objective of this study was to assess the different kinds of pre-harvest and post-harvest losses that maize farmers in Ghana encounter. The storage practices, and farmers’ awareness and knowledge of mycotoxin contamination in maize were also assessed. The study area had five regions, and three districts per region. The study sites were selected purposefully because of the prior knowledge of farmers on maize production. A semi-structured questionnaire was used to collect the data, and a purposive sampling technique was used to select 75 maize farmers for the interview. The male maize farmers were many compared to females. Over 70% of farmers were at least 40 years. Over 50% of farmers had basic education except those in the northern region. Grain yields were generally low, and at least 60% of farmers experienced post-harvest loss. The period of grain storage and the storage techniques were the prerogatives of the farmers but largely dependent on farmers’ financial status. Farmers basically used synthetic chemicals, and a few of the farmers decided to use plant materials during grain treatment.